Physiological evaluation of a new quantitative SPECT method measuring regional ventilation and perfusion - Petersson, Johan; Sanchez-Crespo, Alejandro; Rohdin, Malin; Montmerle, Stephanie; Nyren, Sven; Jacobsson, Hans; Larsson, Stig A; Lindahl, Sten G. E; Linnarsson, Dag; Glenny, Robb W; Mure, Margareta (Journal of applied physiology (1985), 2004)
1 Department of Anesthesiology and Intensive Care, 2 Section of Nuclear Medicine, Department of Hospital Physics, and 5 Department of Radiology, Karolinska Hospital, 171 76 Stockholm; 3 Medical Radiation Physics, Department of Oncology-Pathology, Stockholm University and Karolinska Institutet and 4 Section of Environmental Physiology, Department of Physiology and Pharmacology, Karolinska Institutet, 171 77 Stockholm, Sweden; and 6 Departments of Medicine and Physiology and Biophysics, University of Washington, Seattle, Washington 98195 Submitted 29 January 2003 ; accepted in final form 6 November 2003 We have developed a new quantitative single-photon-emission computed tomography (SPECT) method that uses 113m In-labeled albumin macroaggregates and Technegas ( 99m Tc) to estimate the distributions of regional ventilation and perfusion for the whole lung. The multiple inert-gas elimination technique (MIGET) and whole lung respiratory gas exchange were used as physiological evaluations of the SPECT method. Regional ventilation and perfusion were estimated by SPECT in nine healthy volunteers during awake, spontaneous breathing. Radiotracers were administered with subjects sitting upright, and SPECT images were acquired with subjects supine. Whole lung gas exchange of MIGET gases and arterial P O 2 and P CO 2 gases was predicted from estimates of regional ventilation and perfusion. We found a good agreement between measured and SPECT-predicted exchange of MIGET and respiratory gases. Correlations ( r 2 ) between SPECT-predicted and measured inert-gas excretions and retentions were 0.99. The method offers a new tool for measuring regional ventilation and perfusion in humans. single-photon-emission computed tomography; multiple inert-gas elimination technique; gas exchange Address for reprint requests and other correspondence: J. Petersson, Dept. of Anesthesiology and Intensive Care, Karolinska Hospital, 171 76 Stockholm, Sweden (E-mail: johan.peterssonatks.se ).